Quality of Information Sharing, Agility, and Sustainability of Humanitarian Aid Supply Chains: An Empirical Investigation - Suifan, Taghrid; Alazab, Moutaz; Sweis, Rateb; Abdallah, Ayman; Alhyari, Salah; Saa’da, Raeda (International Journal of Supply Chain Management, 2020)
Abstract— This study aimed to explore the intermediary role of supply chain agility in the relationship between quality of information sharing and sustainability of the humanitarian supply chain. Questionnaire surveys were developed and administered to senior’s managers and assistant executives of the Jordanian Army and Red Crescent. The findings of the data analysis showed that the quality of information sharing positively impacts humanitarian supply chain sustainability. Furthermore, agility in supply chains partially mediates the relationship between quality of information sharing and supply chain sustainability. This study contributes to the existing body of literature on humanitarian aid supply chains by developing a comprehensive framework illustrating the role of inherent mechanisms of agility in the relationship between information-sharing quality and integrating sustainable development objectives, derived from recipients, relief seekers, and stakeholder requirements.